Unraveling chemical glycosylation: DFT insights into factors imparting stereoselectivity - Guo, Aoxin (2024)
Stereoselective chemical glycosylation reactions are pivotal for preparing manifold biologically and medically important compounds, while mechanisms of chemical glycosylation reactions remain obscure and largely speculative. Herein, we performed DFT calculations to delve into the multifaceted mechanistic details of glycosylation reactions, including the equilibria among reactive glycosyl triflate intermediates in solution, the stereoselectivity imparting protecting groups, solvent effects, base, and the anomeric effect. Our results provided theoretical corroboration to 2-OAc neighbouring group participation (NGP), the arming/disarming effect, the coordination theory of solvent effect on glycosylation stereochemistry, and the influence of solvent polarity on the reaction kinetics spanning the SN1-SN2 continuum. For the first time, the existence of putative contact-ion-pairs (CIP) of glycosyl oxocarbenium and triflate anion in organic solutions was theoretically confirmed with the identification of multiple ground state structures employing an implicit Solvation Model based on Density (SMD). Kinetics of nucleophilic attack of model glucosyl triflates by simple alcohol acceptors ethanol (EtOH) and trifluoroethanol (TFE), complexed with 2,4,6-tri-tert-butylpyrimidine (TTBP) were explored, revealing the essential role of the close accompanying base for rendering glycosidic bond formation thermodynamically favourable. Our work deepens the comprehension of the glycosylation mechanism, paving the way for the rational design and future advancement of efficient and environmentally friendly stereoselective glycosylation reactions.